PEMANFAATAN APLIKASI EXPERT CHOICE SEBAGAI ALAT BANTU DALAM PENGAMBILAN KEPUTUSAN (STUDI KASUS: PEMILIHAN PROGRAM STUDI DI UNIVERSITAS SAHID SURAKARTA) - Dwi Retnoningsih (Universitas Sahid Surakarta, 2011)
Making a decision becomes a complicated process if it does not go through the correct steps and is not supported by concrete data. Moreover, it also occurs for the type of unstructured decision making. Because of this type of decision is rare and not easy to be programmed so that the decision-making process should use the fact that is supported by the valid data. One of the example in this case is the choosing of department in a university for new students. It is a complicated process and can allow them to make a mistake. Therefore, to minimize errors in choosing of department in accordance with the ability of students, it needs technology as a tool. This study takes a case study to guide new students in choosing of department at Sahid University of Surakarta. The criteria used in making of this model is based on the assumption of the author trough considering some assessment. The aim of this study is to develop a process decision-making model by using Analytical Hierarchy Process (AHP) and Expert Choice tool (EC) Professional 9.0